The Impact of Cultural Differences on Islamic Public Relations - Rahmawati, Gamayanti Novi; Aung, Nay Lin; Aye, Khin Myo (Journal International Dakwah and Communication, 2024)
Cultural differences play a significant role in shaping public relations (PR) practices, particularly in Islamic contexts where religious values intersect with communication strategies. Islamic public relations (IPR) operates within ethical frameworks derived from Shariah principles, emphasizing honesty, social responsibility, and mutual respect. However, in multicultural and globalized environments, cultural diversity influences message construction, audience reception, and stakeholder engagement. Understanding how cultural variations impact Islamic PR strategies is essential for developing communication models that align with both religious and cultural expectations. This study aims to examine the influence of cultural differences on Islamic PR practices and how organizations adapt communication strategies in diverse socio-cultural contexts. A qualitative research design is employed, combining in-depth interviews with PR professionals from Islamic organizations and content analysis of PR campaigns conducted across different cultural settings. Findings reveal that while Islamic PR maintains ethical consistency, cultural diversity affects messaging, media selection, and engagement approaches. Organizations operating in culturally diverse regions implement localized communication strategies to balance Islamic values with cultural sensitivities. The study concludes that effective Islamic PR requires adaptability, cultural awareness, and ethical alignment to ensure meaningful audience engagement.